Medellín como una representación de la decadencia de Colombia en Casablanca la bella de Fernando Vallejo - Curzytek, Barbara (Studia Romanica Posnaniensia, 2022)
The article analyses the representation of Medellín in Fernando Vallejo’s 2013 novel Casablanca la bella in the context of Zygmunt Bauman’s liquid modernity concept and other cultural theories of the urban, which can be applied to Colombia in the context of omnipresence of violence. The analysis proves that the narrator-protagonist, disappointed with the modernity in Colombian context, is incapable of accepting the changes that the city as well as the country have suffered during his life and uses the descriptions of the urban space for social criticism. The conclusion is that the narrator-protagonist obsessively tries to re-actualize the past and persists in linking to it as he does not see any point of reference in the present nor any positive perspective for Colombia in a foreseeable future.